Proyecto de inversión para el servicio de logística y transporte de carga de mercadería entre las dos ciudades mas importantes del Ecuador - Pilamala Medina., María Fernanda (2009)
The global trend goes to the outsourcing and a company that requires a car fleet chooses the leasing of it, liberated from the concerns of maintaining, procurement and administration of insurance, replacement of a damaged vehicle or in repair, maintenance of municipal permits and carrying daily quota lease costs. Basically the problem that we hope to solve is the lack of supply that companies have to deliver the product to their customers, the transport most used for mobilization of merchandise usually in Quito and Guayaquil are trucks and because of the way they operate the companies incur many expenses than if they hire a service like the one proposed in this project. We experienced today that the way to moving loads, specifically the merchandise is a problem for the companies since the current people that perform this type of transportation is handled in an inappropriate manner, causing many of the goods transported arrives in poor condition to their destination, which is a problem for businesses and high levels of expenditure incurred by problems of returns. Furthermore, this service has no insurance and warranty now, which is an advantage for our business proposition, because our service is intended to meet those needs are not being met.